2022
DOI: 10.1007/s11938-022-00368-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Approach to Incidentally Detected Pancreatic Cystic Lesions

Abstract: Purpose of review The objective of this study is to answer few key questions in order to establish the best possible available diagnostic strategy for incidentally discovered pancreatic cystic lesions (PCLs). Recent findings Advances in EUS-guided sampling techniques, cross-sectional and intracystic confocal imaging, molecular biomarkers analysis, determination of cyst fluid glucose, and artificial intelligence, appear to be associated with an improved dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Conversely, in another meta-analysis [ 64 ] the authors found that if cyst fluid mutational testing for KRAS/GNAS was negative, the probabilities that the patient has an IPMN or a mucinous cystic lesion would be approximately 2% and 8%, respectively [ 65 ], a finding with important practical consequences. These data have been incorporated into the last ACG clinical guideline on the diagnosis and management of pancreatic cysts, which specifically recommend molecular testing of the cyst fluid to be considered in cases in which the diagnosis is unclear, and the results are likely to change management, e.g., in the identification of IPMNs and MCNs [ 11 ].…”
Section: Molecular Testingmentioning
confidence: 99%
“…Conversely, in another meta-analysis [ 64 ] the authors found that if cyst fluid mutational testing for KRAS/GNAS was negative, the probabilities that the patient has an IPMN or a mucinous cystic lesion would be approximately 2% and 8%, respectively [ 65 ], a finding with important practical consequences. These data have been incorporated into the last ACG clinical guideline on the diagnosis and management of pancreatic cysts, which specifically recommend molecular testing of the cyst fluid to be considered in cases in which the diagnosis is unclear, and the results are likely to change management, e.g., in the identification of IPMNs and MCNs [ 11 ].…”
Section: Molecular Testingmentioning
confidence: 99%